The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1631/jzus.b0820116
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline resuscitation reduces apoptosis of intestinal mucosa in a rat model of hemorrhagic shock

Abstract: Abstract:Objective: To investigate the early effects of hypertonic and isotonic saline solutions on apoptosis of intestinal mucosa in rats with hemorrhagic shock. Methods: A model of rat with severe hemorrhagic shock was established in 21 Sprague-Dawley (SD) rats. The rats were randomly divided into the sham group, normal saline resuscitation (NS) group, and hypertonic saline resuscitation (HTS) group, with 7 in each group. We detected and compared the apoptosis in small intestinal mucosa of rats after hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…However, the results of the present study indicated that resuscitation with all three fluids equally restored MAP levels in the early stage of hemorrhagic shock. Although the MAP in rats receiving HTS was slightly lower than those in the other groups at the end of the fluid resuscitation stage, it was still high enough ((97.50±6.83) mmHg) to maintain blood supply to vital organs, based on previous reports (Lu et al, 2010;Barros et al, 2011;Vallet, 2011;Cui et al, 2014). Fluid resuscitation with NS or HES may result in hypoosmolar dehydration, thus stimulating an immune system response and inflammatory injury, whereas HTS may promote a more beneficial state of immunologic stress.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the results of the present study indicated that resuscitation with all three fluids equally restored MAP levels in the early stage of hemorrhagic shock. Although the MAP in rats receiving HTS was slightly lower than those in the other groups at the end of the fluid resuscitation stage, it was still high enough ((97.50±6.83) mmHg) to maintain blood supply to vital organs, based on previous reports (Lu et al, 2010;Barros et al, 2011;Vallet, 2011;Cui et al, 2014). Fluid resuscitation with NS or HES may result in hypoosmolar dehydration, thus stimulating an immune system response and inflammatory injury, whereas HTS may promote a more beneficial state of immunologic stress.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, resuscitation with a small volume (1:5 ratio against blood loss volume) of HTS can stabilize spleen Tregs in the early phase, and may play a beneficial role in reducing immunologic stress after hemorrhagic shock. Indeed previous studies have shown that HTS resuscitation can reduce the injury to lungs and intestinal mucosa after hemorrhagic shock (Fernandes et al, 2009;Gao et al, 2009;Lu et al, 2010). The proposed mechanism by which HTS can mediate these effects is by shrinking cells and mechanically altering membranes, resulting in the release of ATP and promotion of T-cell function (Loomis et al, 2003;Woehrle et al, 2010;Ledderose et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The dosages of HTS and HES were both 1:1 volume to shed blood. The actual dose used in each group was readjusted according to the directions from previous studies (Lu et al, 2008;.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The crystalloid or colloidal solutions, such as normal saline (NS), hypertonic saline (HTS), and hydroxyethyl starch (HES), are widely used fluids in clinical practice and research. Actually, HTS has been already proven to attenuate the increase of some cytokine production and the activity of immune cells in peripheral circulation (Lu et al, 2008;2010;Chen et al, 2011;Motaharinia et al, 2015). It was also found that HES ameliorated oxidative stress and inflammatory response in the rat model during hemorrhagic shock resuscitation (Watters et al, 2006;Wang et al, 2009;Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…In a separate report, the same protocol showed that hemorrhage induced intense apoptosis in the intestinal mucosa; and that this is partially reduced by hypertonic saline resuscitation, but not by resuscitation with normal saline. 24 …”
Section: Lymphocyte Functionmentioning
confidence: 99%